Classification and description of the major farming systems incorporating ruminant livestock in West Africa - Fernández Rivera, S.; Okike, Iheanacho; Manyong, Victor M.; Williams, Timothy O.; Kruska, Russell L.; Tarawali, Shirley A. (International Livestock Research Institute, 2004)
A classification of the major ruminant livestock production systems in West Africa is proposed. The proposed typology has two major classes of systems-sole livestock and crop-livestock. The sole livestock class has two systems (rangeland-based and landless) and the crop-livestock class has three sub-classes (annual crop-livestock, tree-crop-livestock and irrigated/flooded cropland-livestock). Within the 3 crop-livestock subclasses 13 systems defined by the dominant crops are identified. The systems, including the specific roles of crops and livestock are described, their feed production potential is assessed, and the factors likely to be driving their evolution are discussed. The large majority of producers in these systems are poor and their land and animal holdings are small. Pastoral systems evolve in response to risks associated with uncertainty of rain and the demand for live animals in the highly populated and more urbanised wetter zones. Crop-livestock systems are more labour-intensive, in some cases they include animal traction, and are characterised by higher use of agricultural inputs such as fertilisers, pesticides and feed supplements. Landless, stall-feeding systems, which exist alongside or within other systems evolve primarily in response to demand for meat and are frequently associated with religious events. The proposed typology offers a framework for identifying Development priorities and research opportunities. It can assist in targeting efforts to develop animal agriculture into more intensive forms of production with stronger linkages to markets, in ways that the increasing demand for food is met and opportunities for improving the livelihoods of small-scale livestock and crop-livestock producers are exploited.